Ableism and accessibility in higher education: A case study regarding a wheelchair user in a psychology course (Revista Contexto & Educação, 2023)
The purpose of this article is to discuss accessibility and ableism in Higher Education from the academic trajectory of a psychologist with physical disabilities/a wheelchair user. To this end, concepts such as disability, inclusion, accessibility and ableism are discussed. For the production of data, a semi-structured interview was carried out with a wheelchair user, who was invited to speak, among other aspects, about his inclusion in Higher Education in a Psychology undergraduate course. In addition to this interview, the data was complemented by informal conversations to resolve any questions about what had been discussed during the interview. Data analysis followed the principles of Textual Discourse Analysis, with the steps of unitarization, categorization and construction of a metatext. Among the results, the following stand out: ableist manifestations in different situations that influenced the participant’s professional training; aspects related to (in)accessibility to services offered by the university; and a lack of knowledge about the characteristics of academics with disabilities as a disadvantage to their inclusion. As possibilities for advances in improving the quality of inclusion in Higher Education, there should be more dialogue with persons with disabilities, including organizing discussion groups within the university environment as one step towards reducing barriers against inclusion.
Keywords: Accessibility; Ableism; Inclusion in Higher Education; Persons with disabilities